Measurement of Specific Heat of Organic Materials Using Non-Isolating Container and Arduino - Erol, Mustafa; Göl, Damla (Universitas Sebelas Maret, 2023)
This study reports a novel method for specific heat measurements of organic materials namely potaoes, quinces and radishes. The method proposed in this work is novel in the sense that it employs a non-isolated container and an Arduino microprocessors. The actual measurements are simply managed by placing the organic materials within hot water in a non-isolating container and by monitoring the temperature and time by means of Arduino UNO microprocessor. The heat leakage due to the non-isolated container is determined by using the heat versus time graph of the system and by mathematically modeling the temperature decrease by the time due to the heat exchange between the hot water and the environment. The measurements have revealed that the relative errors for the measurements are approximately % 4.75 for potatoes, % 21.50 for radishes and % 1.30 for quinces. The approach described in this work is inexpensive, very easy to apply and can potentially be beneficial for basic physics, science and engineering research activities.